Nilai-Nilai Akhlak Bermasyarakat dalam QS. Al-Hujurat Ayat 11-13: Analisis Penafsiran Imam Al-Maraghi - Ahmad Yasir Sipahutar; Hasyimsyah Nasution (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to explore the moral and social values contained in QS. Al-Hujurāt verses 11–13 through Imam al-Maraghi’s interpretation. The research addresses the issue of declining social ethics, conflicts, and the erosion of moral values in contemporary society. Using a qualitative descriptive-analytical approach and library research method, this study analyzes tafsīr texts, academic literature, and relevant prior studies. The findings reveal four key themes of social ethics: (1) respect for human dignity by prohibiting mockery, insults, and offensive nicknames; (2) preservation of social integrity through the avoidance of slander, prejudice, and fault-finding; (3) universal brotherhood based on human equality across nations and tribes; and (4) piety (taqwa) as the ultimate standard of human virtue. These findings reinforce the theoretical framework of adab ijtima‘i and Qur’anic moral education while highlighting their relevance to preventing social conflict, guiding ethical behavior in digital spaces, and strengthening character education in the era of globalization. In conclusion, this study emphasizes the importance of internalizing Qur’anic values as a moral foundation for modern society and suggests further research on their application in multicultural education and contemporary social practices.